2003
DOI: 10.30843/nzpp.2003.56.6040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parasitism by <i>Aphidius eadyi</i> (Hymenoptera Aphidiidae) on reproduction of pea aphid <i>Acyrthosiphon pisum</i> (Hemiptera Aphididae)

Abstract: The effect of parasitism by Aphidius eadyi Stary González and Hall on reproduction of pea aphid Acyrthosiphon pisum (Harris) was studied in the laboratory Aphids attacked as 1st and 2nd instars became mummies in the 4th instar; parasitised 3rd instar nymphs became mummies in the adult stage without producing any progeny Parasitised 4th instar nymphs and adults produced progeny but had a shorter reproductive period and produced fewer (Plt;00001) progeny than unparasitised aphids Parasitised 4th instar nymphs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Parasitoids that attack early‐instar aphids are likely to be more effective at reducing aphid populations than those that attack late‐instar aphids (Sequeira & Mackauer, ). He et al (, ) found that parasitism of early‐instar PA by A. eadyi prevented any reproduction and, when late instars and adults were parasitized, progeny were still produced but reproductive potential was lower than unparasitized aphids (Fig. ).…”
Section: Trophic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitoids that attack early‐instar aphids are likely to be more effective at reducing aphid populations than those that attack late‐instar aphids (Sequeira & Mackauer, ). He et al (, ) found that parasitism of early‐instar PA by A. eadyi prevented any reproduction and, when late instars and adults were parasitized, progeny were still produced but reproductive potential was lower than unparasitized aphids (Fig. ).…”
Section: Trophic Interactionsmentioning
confidence: 99%
“…Aphid parasitism: P4 , parasitized fourth instar; P, parasitized adult; N, unparasitized adult. Data are the mean ± SE shown after He et al ().…”
Section: Trophic Interactionsmentioning
confidence: 99%
“…Aphids that received a single oviposition strike from the female parasitoid were removed and replaced with unparasitised individuals of the same age until 15 parasitised aphids were collected. Parasitised aphids were placed individually onto a bean plant, which was held in a transparent plastic cylinder (He et al 2003). There were 10 treatments (age classes) and 15 replicates (number of parasitised aphids) for each treatment in this study.…”
Section: Development and Reproductionmentioning
confidence: 99%
“…Many studies have reported that hymenopteran endoparasitoids can reduce the reproductive potential of aphids (Lui & Hughes 1984;Mackauer & Kambhampati 1984;Sequeira & Mackauer 1988;Tang & Yokomi 1996;He et al 2003;Lin & Ives 2003). The majority of these studies indicate that aphids parasitised in their early instars die before reproduction but those parasitised at later stages of development may reach the adult stage and produce a limited number of progeny before mummifi cation.…”
Section: Introductionmentioning
confidence: 99%